The Impact of Career Competence on Career Sustainability Among Chinese Expatriate Managers Amid Digital Transformation in Vietnam: The Role of Lifelong Learning - Zhang, Wei; Chin, Tachia; Li, Fa; Lin, Chien-Liang; Shan, Yi-Nan; Ventimiglia, Francesca (Frontiers in Psychology, 2022)
The digitalization and advanced technologies are replacing human jobs. Around the world, many people lost their jobs due to increasing digitalization. Similarly, Chinese expatriates associated with the manufacturing sector of emerging countries like Vietnam face such challenges. Therefore, Chinese expatriates need to bring competitiveness in their competencies. This competitiveness brings sustainability in their career. The aim of this study to investigate the impact of career competencies on career sustainability. Moreover, we test the mediating effect of lifelong learning in the relationship between career competences and career sustainability. A questionnaire survey approach was used in this study. The target population were the Chinese expatriate managers working at China-invested manufacturing multinational organizations in Vietnam. To estimate the proposed relationships, we use structural equation modeling. The results are confirmed that in the direct relationship career competence has positive impact on career sustainability. The findings of this study also indicate that career competencies have a positive impact on lifelong learning. Furthermore, outcomes confirmed that lifelong learning has a positive impact on career sustainability. Similarly, results are also confirmed that lifelong learning is positively mediating between career competencies on career sustainability. Therefore, the empirical results of this paper identify that lifelong learning has a critical impact on sustainable career. Specifically, this study is useful for the mid-level managers who are associated with multinational organizations. At the end of this paper, we also explained the practical implications, limitations and future research directions.